1999
DOI: 10.1002/(sici)1522-2586(199908)10:2<178::aid-jmri11>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of superficial cartilage lesions: Role of contrast in lesion detection

Abstract: Excised patellar cartilage phantoms with artificial surface lesions were imaged in a 2 g/dl albumin solution to determine the effect of cartilage/fluid contrast on detection of early degenerative change. Surface lesions consisted of full-thickness holes, superficial grooves, and coarse abrasion. Phantoms were imaged with a T1-weighted fast lowangle shot (FLASH) and T2*-weighted dual-echo in the steady state (DESS) sequence. Although both sequences were able to identify full-thickness holes, they underestimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 0 publications
4
37
0
2
Order By: Relevance
“…The relationship between focal cartilage lesions and the overall (global) longitudinal change of cartilage morphology (volumetric tissue loss) is discussed in the following section. (65,(67)(68)(69)(70) (Fig. 4) are currently being investigated in the context of cartilage imaging and have been proposed to provide higher signal efficiency than SPGR (65).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between focal cartilage lesions and the overall (global) longitudinal change of cartilage morphology (volumetric tissue loss) is discussed in the following section. (65,(67)(68)(69)(70) (Fig. 4) are currently being investigated in the context of cartilage imaging and have been proposed to provide higher signal efficiency than SPGR (65).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some investigators suggested that 3D double echo in the steady state (DESS) was useful for cartilage imaging [46,47,48,49]. The 3D DESS images can be generated by combining images from first and second echoes in a steady state and it produces high contrast resolution between cartilage and fluid.…”
Section: Mr Imaging Techniques For Cartilage From Conventional Technimentioning
confidence: 99%
“…These two sequences show synovial fluid with high signal intensity and cartilage with lower signal intensity. Cartilage surface lesions are detected by differences in contrast between synovial fluid and cartilage (12).…”
Section: Introductionmentioning
confidence: 99%